A Collaborative Strategy for Boosting Lithium Storage Performance of Iron Phosphide by Fabricating Hollow Structure and Doping Cobalt Species. Issue 36 (29th September 2020) - Xiao, Jinghao; Zhou, Hu; Wang, Sheng; Yuan, Aihua
Abstract: Transition metal phosphides have received increasing attention in the field of lithium‐ion batteries (LIBs) due to their potential advantages in optimizing electrochemical performances. In order to improve the structural stability and electrochemical reaction kinetics of metal phosphides, it's an effective strategy for introducing foreign metal atoms to isolate bimetallic phosphides. Herein, a metal‐organic‐framework (MOF)‐templated protocol is utilized to synthesize CoFeP hollow nanorods as high‐performance LIBs anode materials. The results reveal that the substitution of Co ions enriches Fe‐based MOF‐derived structure with active sites, meanwhile the Co doping boosts the electronic conductivity. Therefore, the obtained CoFeP electrode displays a superior lithium‐storage ability to single metal phosphide (FeP), in terms of specific capacity, cycle stability, and rate capability. The reversible specific capacity of CoFeP at a current density of 0.1 A g −1 is as high as 897.2 mA h g −1, and the capacity can be still maintained at 478.5 mA h g −1 even at 1 A g −1 after 800 cycles. The intriguing LIBs performance of CoFeP is mainly ascribed to the collaborative contribution of hollow structure and Co doping. Abstract : A collaborative strategy is proposed to boost the lithium storage performance of metal phosphide, which involves the formation of hollow nanostructures and the simultaneous substitution of foreign metal species.